Effects of constant and fluctuating soil temperature on growth, development and nutrient uptake of maize seedlings - Lal, R. (Springer, 1974)
The effect of constant and fluctuating soil temperature and two soil moisture regimes on the growth, development, transpiration and nutrient uptake by maize seedlings was studied in a greenhouse investigation. The constant root temperatures were maintained at 30, 34, 35, 36, 37, and 38°C for both 250 and 750 cm of soil moisture suctions. The fluctuating root temperature, for 250 cm of soil moisture suction only, of 30-35, 30-39, 30-40, 30--45and 30--48°C were maintained to simulate the soil temperature regime under field conditions. The constant root temperature of 35°C and fluctuating temperature between 30-40°C significantly decreased the shoot and root growth and transpiration rate. On the average, there was 1.3 and 0.7 g decrease in fresh shoot weight and 0.36 and 0.30 g in fresh root weight per degree increase in root temperature for 250 and 750 soil moisture suction, respectively. In general, the effect of high soil moisture suction on maize seedlings was more severe when at high root temperature. The shoot and root concentration of N, P, and K decreased while that of B increased with increase in root temperature. The root concentration of Zn also decreased with increase in root temperature.